Analysis Financial Governance and E-Payment to Digitalization Management Finance Public - Nelly, As; Marantika, Abshor (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Study This study effectiveness System​ Information Management Regional Finance (SIPKD) and its implementation e-payment as a digital strategy in increase efficiency, transparency, and accountability management finance public, in line with principles of Good Government Governance (GGG). Meanwhile study previously more Lots focused on approach quantitative with tool analysis statistics like regression, study about context organization and aspects behavior apparatus in utilization system This Still limited. Study This use Mixed Methods Research approach, namely combination analysis quantitative and qualitative. Quantitative data analyzed with statistics descriptive and inferential, while qualitative data analyzed through analysis thematic. The findings indicate that financial understanding, planning, and performance demonstrate relatively stronger outcomes compared to the other assessed aspects, while compliance reporting Still weak. Analysis correlation show existence connection positive between understanding planning and compliance reporting, however variables technical other show very weak relationship with performance finance. The results of the linear regression show that understanding planning, discipline implementation and compliance reporting No influential significant to performance finance. On the other hand, secondary data give proof strong empirical​ that digitalization in a way substantial increase efficiency, transparency, speed data updates, engagement public, and accountability. Study This emphasize importance beyond variables technical solely and taking into account non- technical factors – such as competence source Power human, culture organization, and adoption technology – for truly catch impact digital transformation in management finance public.